A brief narrative on work-related asthma (WRA) - Piryani, Rano Mal; Piryani, Suneel; Sijapati, Milesh Jung (Nepalese Respiratory Journal, 2022)
Work related asthma (WRA) is caused by exposure at work known as occupational asthma (OA) or exacerbated or aggravated by exposure at workplace known as work-exacerbated asthma (WEA) or work-aggravated asthma (WAA). Worldwide, WRA remains under detected and undermanaged. Failure to detect or treat WRA leads to increased healthcare cost, morbidity and mortality. The diagnostic work-up includes clinical history and detailed occupational history, assessment of the causative agent and the objective measurements. Del Roio LC et al (2020) have developed algorithm for the diagnosis of WRA with three primary diagnostic criteria and five additional criteria. Better knowledge and understanding of clinicians and other healthcare providers about WRA is vital for early consideration of WRA diagnosis among adult patients with asthma. While Optimum awareness of general public about WRA may possibly help in initiating discussion by affected workers with their healthcare service providers. The primary prevention includes reducing the burden of WRA by evading the use of potential sensitizers and restricting their exposure and limiting to workplace asthma triggers when their use cannot be avoided.